The Greater Gaza: A Land of Faith, Trade, and Conflict - Shafia Jamil* (Corresponding Author); DR. Hanna-e-Kalbi; Aaliabah Sajjad; Naeem Ahmed (Al-Qanṭara, 2024)
The Palestinian territories of Gaza and the West Bank have been the subject of much conflict and political debate for decades. Jerusalem is a significant religious site for the Abrahamic religions (Judaism, Christianity, and Islam). The Gaza Strip, in particular, has been a symbol of Palestinian strength and resistance against Israeli occupation. The Gaza Strip has a rich historical and cultural significance, with a diverse population of Palestinians. Israel regards the Gaza Strip as significant for several reasons, including its historical and religious significance, security concerns, demographic considerations, and geo-strategic location. It has also been a hub of trade and commerce for centuries, with a strategic location on the Mediterranean coast. It has also been a major trading route for centuries, connecting the Middle East, Europe, and Asia. The water industries have contributed to its value as a trade hub, with desalination plants and wastewater treatment facilities playing a crucial role in the region’s economy. Due Geostrategic placement with Israel and economic significance due ancient trade routes, it also has caught attention of international powers including the United States of America and several other intergovernmental political and economic forums.